Effect of chromium dinicocysteinate supplementation on circulating levels of insulin, TNF-α, oxidative stress, and insulin resistance in type 2 diabetic subjects: Randomized, double-blind, placebo-controlled study - Jain, Sushil K.; Kahlon, Gunjan; Morehead, Lester; Dhawan, Richa; Lieblong, Benjamin; Stapleton, Tommie; Caldito, Gloria; Hoeldtke, Robert; Levine, Steven N.; Bass III, Pat Farrington (Molecular nutrition & food research, 2012)
Scope Chromium and cysteine supplementation have been shown to improve glucose metabolism in animal studies. This study examined the hypothesis that chromium dinicocysteinate (CDNC), a complex of chromium and l‐cysteine, is beneficial in lowering oxidative stress, vascular inflammation, and glycemia in type 2 diabetic subjects. Methods and results Type 2 diabetic subjects enrolled in this study were given placebo for 1 month for stabilization and then randomized into one of three groups: placebo (P), chromium picolinate (CP), or CDNC, after which they received daily oral supplementation for 3 months. Of the 100 patients enrolled in the study, 74 patients completed it. There were 25 patients in the P supplemented group, 25 in the CP supplemented and 24 in the CDNC supplemented group who completed the study. Blood markers of glycemia, vascular inflammation, HOMA insulin resistance, and oxidative stress were determined at randomization and after 3 months of supplementation with P, CP, or CDNC. There was a significant decrease at 3 months in insulin resistance (p = 0.02) and in the levels of protein oxidation (p = 0.02) and TNF‐α (p = 0.01) in the CDNC supplemented cohort compared to baseline. However, there was no statistically significant change in these markers in the CP supplemented group compared to baseline. Insulin levels significantly decreased (p = 0.01) for subjects receiving CDNC but not CP. There was no significant impact of supplementation on HbA1c or glucose levels in either of the groups. Conclusion CDNC supplementation lowers insulin resistance by reducing blood levels of TNF‐α, insulin, and oxidative stress in type 2 diabetic subjects. Therefore, CDNC supplementation has potential as an adjunct therapy for individuals with type 2 diabetes.